Hemodynamic evaluation of endovascular techniques of stenting and coiling for the treatment of internal carotid artery aneurysm: a computational study - Jian Pei; Xiang Xu; Li-Cai Zhao (Scientific Reports)
Abstract The selection optimum endovascular method for the treatment of different cerebral aneurysms has been the main challenge for surgeons. In the present article, the computational technique is used for the hemodynamic evaluation of two main endovascular techniques of stent and coiling for the reduction of the hemorrhage risk of ICA aneurysms. Comprehensive analyses of the blood flow are performed to detect potential regions with high risk at critical stages of the cardiac cycle. Two coiling porosity conditions and stent deformation have been investigated via computational study to reveal the main change related to hemodynamics when these techniques are implemented. The hemodynamic results of this study show that the endovascular technique is more efficient in small aneurysms rather than giant ones. Meanwhile, the stent treatment of the giant saccular aneurysm is effective when the parent vessel of this type of aneurysm is fully aligned and limited blood flow enters the sac area.